THE ESSENCE OF GRANTING THE RIGHT OF DENIAL FOR NOTARY OFFICIALS IN LAW ENFORCEMENT PROCESSES - Putu Eka Trisna Dewi; Ridwan Sidharta (NOTARIIL Jurnal Kenotariatan, 2022)
Article 4 and Article 16 paragraph (1) letter f of UUJN oblige a Notary to maintain the confidentiality of everything about the deed he or she made as well as all information obtained that is necessary for making the deed in accordance with their oath of office, unless the law provides otherwise. This research aims to examine the essence of the right of denial for notaries in performing duties in accordance with the UUJN and to examine the consequences of the right of denial for notaries in the law enforcement process. The type of research used in this research is normative legal research and the approach used in this research is a statute approach and a legal concept approach. Based on analysis, it was found that if a Notary, who has been given the trust and has been sworn in in accordance with Article 4 of the UUJN concerning the Oath of Notary Position and also Article 16 paragraph (1) letter e of the UUJN concerning Notary Obligations, keeps the contents of the deed a secret, violating the oath, then he or she may be penalized. The consequence of the secrecy of the position held by a Notary in terms of providing testimony about the status of their right of denial is that the notary concerned will be disqualified if then the judge still rejects the application for the right of denial of the Notary in the trial, outside the exception to the law.